2021
DOI: 10.1182/bloodadvances.2021004424
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin is a novel cell surface disease marker and potential therapeutic target in acute myeloid leukemia

Abstract: In an effort to identify acute myeloid leukemia (AML)-restricted targets for therapeutic development in AML, we analyzed the transcriptomes of 2051 children and young adults with AML and compared the expression profile with normal marrow specimens. This analysis identified a large cohort of AML-restricted genes with high expression in AML, but low to no expression in normal hematopoiesis. Mesothelin (MSLN), a known therapeutic target in solid tumors, was shown to be highly overexpressed in 36% of the AML cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 63 publications
1
29
1
Order By: Relevance
“…15 Thus, MSLN is a promising target for multiple diseases. 16 These data showed that MSLN is indeed highly expressed in AML but essentially absent in the normal bone marrow. Transcriptome sequencing (RNA sequencing) of MSLN-positive AML and solid tumors shows substantial overlap in the MSLN expression level, which indicates that MSLN profiles in these 2 types of tumors are similar.…”
Section: Mslnmentioning
confidence: 81%
See 3 more Smart Citations
“…15 Thus, MSLN is a promising target for multiple diseases. 16 These data showed that MSLN is indeed highly expressed in AML but essentially absent in the normal bone marrow. Transcriptome sequencing (RNA sequencing) of MSLN-positive AML and solid tumors shows substantial overlap in the MSLN expression level, which indicates that MSLN profiles in these 2 types of tumors are similar.…”
Section: Mslnmentioning
confidence: 81%
“…However, MSLN expression was rare or absent in FLT3-ITD-, NPM1-, and CEBPα-mutated AML patients. 16,25 In summary, MSLN is indeed highly expressed in AML patients with specific genotypes, and it is not expressed in hematopoietic cells.…”
Section: Mslnmentioning
confidence: 92%
See 2 more Smart Citations
“…To date, the etiology of leukemia has not been fully clear, and current studies suggest that chemical factors, radiation factors, genetic factors and immune factors play important roles in the pathogenesis of leukemia [ 8 ]. The immune system’s role in the occurrence and development of tumors is highly complex.…”
Section: Introductionmentioning
confidence: 99%